Nucleotide variation in Foxp3 gene and prognosis of bladder cancer: a case-control study - Li, Qin; Zhang, Yan; Su, Min; Song, Yaping; Wang, Yanyun; Zhou, Bin; Zhang, Lin (Frontiers in Oncology, 2025)
BackgroundNumerous researches have investigated the correlation between single nucleotide polymorphisms (SNPs) in the transcription factor forkhead box protein 3 (Foxp3) gene and the development of various cancers. However, the relationship of Foxp3 polymorphism and bladder cancer (BC) remain unclear.MethodThis hospital-based case-control study enrolled a total of 316 patients diagnosed with BC and 643 healthy controls. Two Foxp3 SNPs (rs3761548 C/A, rs5902434 del/ATT) were selected, and genotyping of the samples was performed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. SPSS and online SNPstats software were used to determine the disparities between groups.ResultsFor the rs3761548 C/A polymorphism, patients with the CA/AA genotype showed a notable decrease in the case group (22.1% versus 34.8%, P = 0.003, OR = 0.61, 95%CI = 0.44-0.85), and the heterozygous CA genotype presented a distinctly lower risk for BC (P = 0.0003, OR = 0.43, 95%CI = 0.26-0.70). Notably, individuals who were homozygous for the AA genotype demonstrated a markedly lower overall survival (OS) rate compared to those with the CC/CA genotypes (P = 0.03, OR = 5.89, 95%CI = 1.23-28.15), after adjusting for factors such as age, gender, smoking status, tumor grade, metastasis, and clinical stage. For the rs5902434 del/ATT polymorphism, a decreased risk was observed across the codominant and over-dominant models with statistical significance (codominant model: P = 0.01, OR = 0.61, 95%CI = 0.42-0.89; over-dominant model: P = 0.004, OR = 0.60, 95%CI = 0.42-0.85), and no significant association was observed between the rs5902434 polymorphism and patient’s OS rate.ConclusionsOur findings indicate that Foxp3 polymorphisms may be associated with BC susceptibility, and that rs3761548 could potentially serve as an independent risk factor for the OS rate.